Agile Parameter Affecting Supply Chain Management Strategy - Aarti Karande; Dhananjay Kalbande (International Journal of Supply Chain Management, 2017)
The aim of this paper is to summarize Supply Chain Management (SCM) strategies which are getting affected by the agile parameters. Agile parameters are classified into Capabler, Driver, and Enabler may help an expert to take a decision in an agile environment for accepting changes. Agile development affects the working style of the modules in SCM. This paper shows business process agility defined by the number of the parameter affecting the working style of the SCM modules. The study includes a causal analysis of SCM modules based on the review of a number of research papers and books. SCM based case study of inventory management of swatches is studied with the strategy mapping in different modules based on agile parameters. Set of parameters is studied as per the case study of swatch inventory management in agile development. Mapping agile parameters at different strategies in the changing environment makes a system to understand the impact and future of the agile parameters at different levels of SCM modules. Finding the different type of agility and amount of agility in the SCM system can be an enhancement of this paper.